An effective method for computer network anomaly detection. (December 2020) - Wang, Dongpo; Zhao, Chengli; Zhang, Xue; Liu, Boyu; Li, Xiang; Yi, Dongyun
Abstract: With the increasing network threat, network anomaly detection has become a very challenging and indispensable task. In this article, we propose an anomaly detection algorithm through modeling computer network as temporal network. The active subnetwork is extracted from the original computer communication network and then projected to an undirected weighted network series, finally the abnormal behavior patterns of network series are detected based on eigenvectors. Data test experiment shows that the proposed algorithm has achieved very good results.